Przyjaźń w życiu i twórczości Klemensa Janickiego - Bering, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The present paper focuses on friendship’s role in life and poetry of Klemens Janicki (1516–1543). Unfortunately there is a noticeable lack of sources and testimonies. The analysis of poetical works written by Janicki is only partially useful. In the epoch of the Renaissance very often the statements on friendship were exaggerated. Despite of these circumstances it is possible to analyze the poetical techniques used in texts about friends and friendship. The paper ends with an attempt to describe the nature of Ianicius’ relationships with his friends.